Extended adjuvant temozolomide in newly diagnosed glioblastoma: A single-center retrospective study - Chen, Jie; Wang, Tingting; Liu, Wanming; Qiu, Hui; Zhang, Nie; Chen, Xueting; Ding, Xin; Zhang, Longzhen (Frontiers in Oncology, 2022)
Objective To investigate whether extending adjuvant temozolomide (TMZ) improved the prognosis of newly diagnosed glioblastoma (GBM) patients with different mutation statuses of O6-methylguanine DNA methyltransferase (MGMT), isocitrate dehydrogenase 1 (IDH1), p53 and different expression level of Ki67. Methods Postoperative patients with newly diagnosed GBM who did not progress after receiving radiotherapy with concomitant and 6 cycles of adjuvant TMZ were enrolled in control group, and those received more than 6 cycles of adjuvant TMZ were incorporated in extended group. Patients were stratified by MGMT methylation, IDH1 mutation, p53 mutation and expression level of Ki67. The primary endpoints were overall survival (OS) and progression-free survival (PFS). Result A total of 93 postoperative patients with newly diagnosed GBM were included in this study, 40 and 53 cases were included in control group and extended group, respectively. On the whole, extended adjuvant TMZ chemotherapy significantly prolonged OS and PFS of patients with newly diagnosed GBM [median OS (mOS): 29.00 months vs. 16.70 months, P < 0.001; median PFS (mPFS): 13.80 months vs. 9.60 months, P = 0.002]. The results of subgroup analysis showed that patients with methylated MGMT in extended group had significantly longer OS and PFS than those in control group; patients with IDH1 mutation benefited more from extended adjuvant TMZ chemotherapy than those with wild-type IDH1; there was no significant difference in the effect of extended TMZ chemotherapy on OS between GBM patients with wild-type p53 and those with mutant p53; compared with GBM patients with lower expression of Ki67, extended adjuvant TMZ treatment dramatically improved the OS and PFS of those with higher expression of Ki67. Conclusion The therapeutic schedule of extended adjuvant TMZ significantly prolonged OS and PFS of patients with newly diagnosed GBM regardless of p53 mutation status, and patients with different MGMT methylation, IDH1 mutation and Ki67 expression level benefited differently from extended adjuvant TMZ chemotherapy.